การใช้ห้องสมุดเพื่อเพิ่มประสิทธิภาพการจัดการเรียนรู้ของตัวเองในห้วงหลังการระบาด ของโรคติดเชื้อไวรัสโคโรนา 2019 หรือโควิด 19 - ดีโพธิ์กลาง, ทัศนี (วารสารมหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน; Vol 1 No 2 (2020): พฤษภาคม - สิงหาคม 2563, 2020)
บทคัดย่อ การใช้ห้องสมุดเพื่อการเพิ่มประสิทธิภาพการจัดการเรียนรู้ของตนเอง ผู้เรียนรู้ต้องพัฒนาตนเองให้มีทักษะแบบรู้รอบด้าน เข้าใจโลกได้หลากหลายมิติเช่นกัน รวมทั้งมีความกระตือรือร้นเห็นอกเห็นใจผู้อื่นมากขึ้นสิ่งเหล่านี้จะเพิ่มความสำคัญขึ้นอย่างมากในยุคโควิด-19 และจะกลายเป็นหัวใจสำคัญของการศึกษาในอนาคต ส่วนด้านเทคโนโลยีสามารถปรับประสบการณ์การเรียนรู้ให้ตรงกับความต้องการของแต่ละคนได้ แต่สถานศึกษาหรือผู้เกี่ยวข้องต้องมองผู้เรียนแบบใหม่สอดรับกับโลกใหม่รวมถึงออกแบบระบบใหม่เพื่อให้ผู้เรียนสามารถเรียนรู้ได้ด้วยตัวเอง สิ่งสำคัญที่ไม่ควรมองข้ามคือต้องจัดระบบห้องสมุดให้เหมาะสมกับสถานการณ์ของโรคระบาด (โควิด-19) เนื่องจากโรคดังกล่าวยังไม่มีตัวยารักษาให้หายอย่างเด็ดขาด เหตุการณ์เช่นนี้มีส่วนทำให้แรงจูงใจในการเรียนรู้ลดลง หากไม่มีบรรยากาศการเรียนรู้เหมาะสม แต่ผู้เรียนต้องร่วมสร้างบรรยากาศที่ดีในการเรียนรู้ด้วย เพราะในที่สุดแล้วคน ๆ หนึ่งจะต้องรับผิดชอบขวนขวายในการเรียนรู้ของตัวเองไปตลอดชีวิต  Abstract Using libraries to enhance their Self-Directed Learning. Learners need to develop themselves to have comprehensive knowledge. Can understand the world in many dimensions as well as being more enthusiastic and empathetic, these will be of great importance in the COVID-19 era. And will become the heart of education in the future Technology can tailor the learning experience to the needs of each individual. But educational institutions or stakeholders need to look at the learners in a new way, in line with the new world, and to design a new system so that learners can learn by themselves. It is important not to be overlooked that the library system should be organized to suit the situation of the epidemic (COVID-19) since the disease has no cure for the cure. These incidents contribute to a decrease in motivation for learning. If there is no suitable learning atmosphere But the students must also contribute to creating a good learning environment. Because in the end people One has to be committed to his own learning for the rest of his life.